Perlindungan Hukum Bagi Pencipta Atas Pembajakan Film Di Era Digital Guna Memberikan Kepastian Hukum - Furqon, Muhammad; Rosmidah, Rosmidah (Universitas Jambi, Fakultas Hukum, 2025)
This research highlights the continued weakness of legal protection against the rapidly growing practice of film piracy in the digital era, especially through platforms such as Telegram and illegal streaming sites. The main objective of this study is to identify and analyze applicable legal provisions, as well as to evaluate the effectiveness of government policies in ensuring legal certainty for film creators. The method used is a normative juridical approach, by examining laws and regulations, socio-legal dynamics, and relevant case studies. Research data is sourced from primary, secondary, and tertiary legal materials, which are analyzed deductively to produce a deep and systematic understanding. The main findings indicate that legal protection against digital copyright infringement has not been effective, due to the ambiguity of norms in Article 40 paragraph (1) letter m and Article 55 paragraph (1) of Law Number 28 of 2014, which hinders the law enforcement process. This regulatory inaccuracy indicates that existing legal instruments have not been able to address the complexity of violations in the constantly evolving digital space. Therefore, it is concluded that legal reforms are needed that are more firm and responsive to the development of information technology, as well as increased coordination among related institutions, in order to create a comprehensive legal protection system capable of protecting both the economic and moral rights of cinematographic creators.